The Transcription Factor C-Myc Suppresses MiR-23b and MiR-27b Transcription during Fetal Distress and Increases the Sensitivity of Neurons to Hypoxia-Induced Apoptosis - Chen, Qun (PLoS One, 2015)
Previous studies reported that the expression of miR-23b-27b cluster was downregulated in embryonic brain cortices during hypoxia-induced neuronal apoptosis. However, the mechanism underlying this downregulation is not completely understood. Here, we report that the transcription factor c-Myc plays an important role in regulating the expression of miR-23b-27b cluster during hypoxia. First, the c-Myc protein level was significantly elevated in embryonic brain cortices in a mouse model of fetal distress. Second, forced overexpression or knockdown of c-Myc could suppress or increase the expression of miR-23b-27b cluster polynucleotides. Third, we identified 2 conserved c-Myc binding sites (E-boxes) in the enhancer and promoter regions of miR-23b-27b cluster in the mouse genome. Finally, we showed that elevated c-Myc expression led to an increase in the Apaf-1 level by suppressing miR-23b-27b cluster expression and that this enhanced neuronal sensitivity to apoptosis. In summary, our study demonstrates that c-Myc may suppress the expression of the miR-23b-27b cluster, resulting in additional neuronal apoptosis during hypoxia.